Paradigma Governansi dalam Tata Kelola Pemerintahan Daerah: Studi Kasus Kabupaten Bintan - Indah Dwi Lestari; Dela Afrilia (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines governance theory as a transformative paradigm in local government management, with a particular focus on the maritime sector in Bintan Regency. Governance represents a shift from a hierarchical government model to a more collaborative, participatory, and network-based model involving various stakeholders, including government institutions, local communities, and the private sector. Using a descriptive qualitative approach, the study utilizes secondary data sources, including local government reports, academic publications, and related policy documents. The findings show that Bintan Regency has begun to implement governance principles through multisectoral cooperation, community empowerment, and sustainable marine programs. However, the implementation of governance in maritime management in Bintan still faces challenges, such as weak institutional capacity, overlapping authority, and limited human resources. This study concludes that the governance paradigm provides a strategic foundation for building a participatory, transparent, and sustainable framework for maritime management at the local level. Therefore, it is essential to continue addressing these challenges to ensure that governance can be more effective in improving the management of maritime resources in Bintan.